Proteoforms Concept and Applications in Medical Sciences - Zhan, Xianquan (IntechOpen, 2020)
A proteoform is the basic unit in a proteome, defined as its amino acid sequence + post-translational modifications + spatial conformation + localization + cofactors + binding partners + a function, which is the final functional performer of a gene. Studies on proteoforms offer in-depth insights and can lead to the discovery of reliable biomarkers and therapeutic targets for effective prediction, diagnosis, prognostic assessment, and therapy of disease. This book focuses on the concept, study, and applications of proteoforms. Chapters cover such topics as methodologies for identifying and preparing proteoforms, proteoform pattern alteration in pituitary adenomas, and proteoforms in leukemia.